PERAN BABINSA DALAM KEGIATAN DETEKSI DINI GUNA PENCEGAHAN AKSI TERORISME (RELEVANSI DI WILAYAH KODIM 0618/BS KOTA BANDUNG) - KOMARUDDIN S., KOMARUDDIN S. ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This research was intended to find out the roles of Babinsa in support of early detections efforts in order to prevent terorism, to look for any troubles among the Babinsa during performing their tasks to prevent terorism and to formulate empowering efforts to support Babinsa roles in early detection to prevent terorism. The methodologies employed in this research was research based on qualitative approach which data collection techniques as follows